2011
DOI: 10.1074/jbc.m111.253393
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Membrane Activity of the Cyclotide Kalata B1

Abstract: Cyclotides, a large family of cyclic peptides from plants, have a broad range of biological activities, including insecticidal, cytotoxic, and anti-HIV activities. In all of these activities, cell membranes seem likely to be the primary target for cyclotides. However, the mechanistic role of lipid membranes in the activity of cyclotides remains unclear. To determine the role of lipid organization in the activity of the prototypic cyclotide, kalata B1 (kB1), and synthetic analogs, their bioactivities and affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 60 publications
9
117
1
1
Order By: Relevance
“…1A) to isomerize, leading to the formation of succinimide and b-aspartyl isomers as observed in earlier reports [12,13]. Regardless, both isomers undergo backbone cyclization in the presence of m 4 SrtA, as observed by the shift in their retention times and molecular weights ( Fig. 2B and D, peaks 1 ⁄ and 2 ⁄ ).…”
Section: Sortase A-mediated Cyclization Of Rmcoti-iisupporting
confidence: 48%
See 4 more Smart Citations
“…1A) to isomerize, leading to the formation of succinimide and b-aspartyl isomers as observed in earlier reports [12,13]. Regardless, both isomers undergo backbone cyclization in the presence of m 4 SrtA, as observed by the shift in their retention times and molecular weights ( Fig. 2B and D, peaks 1 ⁄ and 2 ⁄ ).…”
Section: Sortase A-mediated Cyclization Of Rmcoti-iisupporting
confidence: 48%
“…This strategy led to the identification of four amino acid mutations P94S/D160N/D165A/K196T within the catalytic domain of Sortase A (Q60-K206) that, when combined, resulted in a 140-fold increase in k cat /K m . We generated this mutant Sortase A (referred to as m 4 SrtA) and confirmed that the reaction kinetics were indeed significantly improved over the wild-type enzyme (Supp. Fig.…”
Section: Sortase A-mediated Cyclization Of Rmcoti-iimentioning
confidence: 83%
See 3 more Smart Citations